Gene expression and chromatin structure in the pre-implantation embryo - Kanka, J (Theriogenology, 2003)
The pre-implantation period of mammalian development includes the formation of the zygote, the activation of the embryonic genome (EGA), and the beginning of cellular differentiation. During this period, protamines are replaced by histones, the methylated haploid parental genomes undergo demethylation following formation of the diploid zygote, and maternal control of development is succeeded by zygotic control. Superimposed on this activation of the embryonic genome is the formation of a chromatin-mediated transcriptionally repressive state requiring enhancers for efficient gene expression. The development of this transcriptionally repressive state most likely occurs at the level of chromatin structure, because inducing histone hyperacetylation relieves the requirements for enhancers. Characterization of zygotic mRNA expression patterns during the pre-implantation period and their relationship to successful development in vitro and in vivo will be essential for defining optimized culture conditions and nuclear transfer protocols. The focus of this review is to summarize recent advances in this field and to discuss their implications for developmental biology.
Keywords: histony; prasata; Cattle; Swine; vývojová regulace genové exprese; skot; Embryonic Development; Gene Expression Regulation, Developmental; zygota; Pregnancy; těhotenství; králíci; chromatin; Chromatin; Animals; ženské pohlaví; zvířata; Rabbits; embryonální vývoj; Histones; Zygote; Female